Semiotics in the age of disruptive innovations - SURAPONGSE, S. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The state of signs and language is unstable. As it is fluid, it must present itself freely without intermittent barriers. The change in disruptive innovation is a key factor in making sign language / fluent language no longer static or frozen, so that we cannot separate truth from falsehood, real things from illusions, and freedom from confusion. Disruptive innovation makes digital concepts replace analog ones, making possible the dualistic approach of signs in the development of software processing. RESUMEN El estado de los signos y el lenguaje es inestable. Al ser fluido debe presentarse libremente sin barreras intermitentes. El cambio en la innovación disruptiva es un factor clave para que el lenguaje de señas / lenguaje fluido, ya no sea estático o congelado, de modo que no podamos separar la verdad de la falsedad, las cosas reales de las ilusiones y la libertad de la confusión. La innovación disruptiva hace que los conceptos digitales reemplacen a los analógicos, lo que hace posible el enfoque dualista de los signos en el desarrollo del procesamiento del software.